Body dimensions and weight to height indices in rescuers from the State Fire Service of Poland - Wiśniewski, Andrzej; Jarosz, Wojciech; Czajkowska, Anna; Mróz, Anna; Smolarczyk, Marcin; Magiera, Andrzej; Kowalczyk, Przemysław; Zimmerman-Rysz, Dagmara; Kowalczyk, Marek (Anthropological Review, 2018)
Few studies have been published in Poland concerning body dimensions of firefighters from the State Fire Service although this knowledge is needed for e.g. development of personal protective equipment. The aim of the study was to evaluate body dimensions and weight-to-height ratio in firefighters from the State Fire Service. Using the anthropological procedures, body mass (BM) and body height (BH) were examined in 178 men at the chronological age (CA) of 19.5 to 53 years who were rescuers from the national rescue and fire brigades of the State Fire Service. The study participants were divided into three categories of CA: up to 25 years, between 24 and 44 years, and over 44 years. The results were compared to population standards. It was found that BH of the youngest rescuers was significantly higher (0.05) than in other study participants. Based on the standardized values of BM and BMI, population of firefighters aged over 25 years was found to be characterized by overweight and, in certain cases, even by obesity. The excess level of body mass index (BMI ≥ 25 kgm2) was found in nearly 60% of study participants, with half of the group classified as overweight (n=31, BMI ranging from 25 to 29.9 kg/m2), and 10% classified as obese. Due to the worrying high percentage of cases of excess body mass in firefighters from the State Fire Service, it was found that it is recommended to evaluate the relationships between body height and mass on regular basis during periodical obligatory tests of physical fitness of rescuers from the State Fire Service and to increase the frequency and duration of training sessions.